The spaced learning concept significantly improves training for laparoscopic suturing: a pilot randomized controlled study - Boettcher, Michael; Boettcher, Johannes; Mietzsch, Stefan; Krebs, Thomas; Bergholz, Robert; Reinshagen, Konrad (Surgical endoscopy, 2018)
Background Spaced learning has been shown to be effective in various areas like traditional knowledge or motor skill acquisition. To evaluate the impact of implementation of the spaced learning concept in laparoscopic training was the aim of this study. Methods To evaluate the effectiveness of spaced learning, subjects were asked to perform four surgeon’s square knots on a bowel model prior and post 3 h of hands-on training. All subjects were medical students and novice in laparoscopic suturing. Total time, knot stability (evaluated via tensiometer), suture accuracy, knot quality (Muresan score), and laparoscopic performance (Munz checklist) were assessed. Moreover, motivation was accessed using Questionnaire on Current Motivation. Results Twenty students were included in the study; after simple randomization, ten were trained using “spaced learning” concept and ten conservatively. Both groups had comparable baseline characteristics and improved after training significantly regarding all aspects assessed in this study. Subjects that trained via spaced learning were superior in terms of suture performance, knot quality, and suture strength. Ultimately, spaced learning significantly decreased anxiety and impression of challenge compared to controls. Conclusion The spaced learning concept is very suitable for complex motor skill acquisition like laparoscopic suturing and knot tying. It significantly improves laparoscopic performance and knot quality as shown by the knot score and suture strength. Thus, we recommend to incorporate spaced learning into training courses and surgical programs.